PENGARUH KONFLIK DAN STRESS KERJA TERHADAP KINERJA KARYAWAN PT. DELIMA PINGLOGISTRA JAKARTA TIMUR - Tini Juartini (Jurnal Ekonomi dan Industri, 2021)
This study aims to determine the effect of conflict and work stress on employee performance by conducting research at PT Delima Pinglogistra, East Jakarta. Researchers conducted research using a questionnaire with a sample of 66 people with the analytical technique used using multiple regression. Based on the data obtained, it can be concluded in this study that the effect of conflict and work stress can simultaneously affect employee performance at PT. Delima Logistra, East Jakarta. The purpose of this study was to determine the effect of conflict and work stress on employee performance at PT. Pomegranate Pinglogistra, East Jakarta.